Progress in the development of modulators targeting Frizzleds - Junlan Chuan; Wei Li; Shengliu Pan; Zhongliang Jiang; Jianyou Shi; Zhenglin Yang (Elsevier, 2024)
The Frizzleds (FZDs) receptors on the cell surface belong to the class F of G protein-coupled receptors (GPCRs) which are the major receptors of WNT protein that mediates the classical WNT signaling pathway and other non-classical pathways. Besides, the FZDs also play a core role in tissue regeneration and tumor occurrence. With the structure and mechanism of FZDs activation becoming clearer, a series of FZDs modulators (inhibitors and agonists) have been developed, with the hope of bringing benefits to the treatment of cancer and degenerative diseases. Most of the FZDs inhibitors (small molecules, antibodies or designed protein inhibitors) block WNT signaling through binding to the cysteine-rich domain (CRD) of FZDs. Several small molecules impede FZDs activation by targeting to the third intracellular domain or the transmembrane domain of FZDs. However, three small molecules (FZM1.8, SAG1.3 and purmorphamine) activate the FZDs through direct interaction with the transmembrane domain. Another type of FZDs agonists are bivalent or tetravalent antibodies which activate the WNT signaling via inducing FZD-LRP5/6 heterodimerization. In this article, we reviewed the FZDs modulators reported in recent years, summarized the critical molecules' discovery processes and the elucidated relevant structural and pharmacological mechanisms. We believe the summaried molecular mechanisms of the relevant modulators could provide important guidance and reference for the future development of FZD modulators.